Implementation of the Principle of Discrete-Pulse Energy Input to the Creation of Nanotechnologies for Food Industry - Avdieieva, L.I. (Science and Innovation, 2024)
The expediency of using the principle of discrete-pulse energy input in directional control of lipid nanostructures formation and industrial production of functional materials with them in order to reduce energy consumption and increase process productivity has been substantiated. The example of using lipid nanostructures for improving a new type of food for special dietary purpose has been given.